Crosstalk between periodontitis and cardiovascular risk - Schulze-Späte, Ulrike; Wurschi, Ludwig; van der Vorst, Emiel P. C.; Hölzle, Frank; Craveiro, Rogerio B.; Wolf, Michael; Noels, Heidi (Frontiers in Immunology, 2024)
Recent demographic developments resulted in an aged society with a rising disease burden of systemic and non-communicable diseases (NCDs). In cardiovascular disease (CVD), a NCD with high morbidity and mortality, recent preventive strategies include the investigation of comorbidities to reduce its significant economic burden. Periodontal disease, an oral bacterial-induced inflammatory disease of tooth-supporting tissue, is regulated in its prevalence and severity by the individual host response to a dysbiotic oral microbiota. Clinically, both NCDs are highly associated; however, shared risk factors such as smoking, obesity, type II diabetes mellitus and chronic stress represent only an insufficient explanation for the multifaceted interactions of both disease entities. Specifically, the crosstalk between both diseases is not yet fully understood. This review summarizes current knowledge on the clinical association of periodontitis and CVD, and elaborates on how periodontitis-induced pathophysiological mechanisms in patients may contribute to increased cardiovascular risk with focus on atherosclerosis. Clinical implications as well as current and future therapy considerations are discussed. Overall, this review supports novel scientific endeavors aiming at improving the quality of life with a comprehensive and integrated approach to improve well-being of the aging populations worldwide.